2006
DOI: 10.1002/cne.20973
|View full text |Cite
|
Sign up to set email alerts
|

Long hydrocarbon chains serve as unique molecular features recognized by ventral glomeruli of the rat olfactory bulb

Abstract: In an effort to understand mammalian olfactory processing, we have been describing the responses to systematically different odorants in the glomerular layer of the main olfactory bulb of rats. To understand the processing of pure hydrocarbon structures in this system, we used the [ 14 C]2-deoxyglucose method to determine glomerular responses to a homologous series of alkanes (from six to sixteen carbons) that are straight-chained hydrocarbons without functional groups. We found two rostral regions of activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 70 publications
8
48
0
Order By: Relevance
“…The phenomenon is seen for both primary alcohols and secondary alcohols with the hydroxyl group in the 2-position . The hydrocarbon chain-related domains (light blue in Figure 4) also show chemotopic progressions for all effective stimuli including esters, acids, alcohols, aldehydes, and alkanes (Johnson et al, 1998;2004;Inaki et al, 2002;Igarashi and Mori, 2005;Ho et al, 2006a).…”
Section: Chemotopic Progressions Within Glomerular Modulesmentioning
confidence: 99%
See 3 more Smart Citations
“…The phenomenon is seen for both primary alcohols and secondary alcohols with the hydroxyl group in the 2-position . The hydrocarbon chain-related domains (light blue in Figure 4) also show chemotopic progressions for all effective stimuli including esters, acids, alcohols, aldehydes, and alkanes (Johnson et al, 1998;2004;Inaki et al, 2002;Igarashi and Mori, 2005;Ho et al, 2006a).…”
Section: Chemotopic Progressions Within Glomerular Modulesmentioning
confidence: 99%
“…For example, habituation among members of a homologous series of aliphatic acids or alkanes was proportional to the degree of similarity in their 2DG activity patterns (Cleland et al, 2002;Ho et al, 2006a). Quantitative similarities between 2DG patterns evoked by octane and/or by eightcarbon branched alkanes or eight-carbon alkenes and alkynes also predicted the amount of cross-habituation between the odorant pairs (Ho et al, 2006b).…”
Section: Cross-habituationmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice and humans the dorsal part of the OB was implicated in innate responses to aversive odorants (Kobayakawa et al, 2007;Rolls et al, 2003). Several studies have found a relationship between differences in behavior and shifts in spatial patterns (Ho et al, 2006;Linster et al, 2002) and, even more, changing locations of glomeruli in mice can result in behavioral impairments, in spite of persistent physiological activations (Adam and Mizrahi, 2010). Similarly, in the AL of female moths, glomeruli in a sexually dimorphic region specialize in odorants that are related to oviposition (Kalberer et al, 2010;Reisenman et al, 2009).…”
Section: Physiologymentioning
confidence: 99%